OPTIMIZATION OF ECO-FRIENDLY CHEMICALS ON ALTERNARIA BLIGHT DISEASE PROGRESSION AND YIELD COMPONENTS OF MUSTARD - AMARENDRA KUMAR; RAKESH KUMAR; SANTOSH KUMAR; GIREESH CHAND; S. J. KOLTE (The Bioscan, 2015)
The significantly minimum average size of spot was observed in KCl at 1.0% (2.02 mm) followed by Na2B4O7.10H2O at 0.75% (2.09 mm) and CaSO4 at 0.5% (2.12 mm) in comparison to check (2.83 mm).The minimum average number of leaf spots/25 mm2 area was found in CaSO4 at 1.5% (5.79) followed by CaSO4 at 0.5% (5.97) in comparison to check (9.29). The minimum average apparent infection rate on leaf was recorded in CaSO4 at 0.5% (0.616) followed by CaSO4 at 1.5% (0.633) and Na2B4O7.10H2O at 0.75% (0.638). The minimum AUDPC was observed in Na2B4O7.10H2O at 0.75% (59.6 mm2) followed by CaSO4 at 0.5% (61.25 mm2) and KCl at 1.0% (61.55 mm2). The minimum apparent infection rate on pod was observed in treatment Na2B4O7.10H2O at 0.75% in the observation intervals 80-90 DAS and 100-110 DAS (0.517 and 0.754, respectively) while in the observation interval 90-100 DAS, minimum apparent infection rate was found in Na2B4O7.10H2O at 0.25% (0.667). CaSO4 at 1.0% showed maximum seed yield/plant (8.54 g) and total yield/ha (1.91 t/ha) in comparison to check. This study suggested that CaSO4 providing the maximum reduction of alternaria blight disease and enhanced the maximum yield of mustard.